Home Blood Pressure Monitoring dan Health Education pada Manajemen Hipertensi Kehamilan - Nicky Danur Jayanti; Senditya Indah Mayasari (Oksitosin : Jurnal Ilmiah Kebidanan, 2024)
The incidence of hypertension in pregnancy occurs in 5 – 10 out of 100 pregnant women. Home blood pressure monitoring (HBPM) is a method of screening blood pressure at home. Pregnant women with hypertension also need health education as an effort to live a healthier life. This research aims to determine the effectiveness of HBPM and Health Education in reducing blood pressure in pregnant women. Quasi-experimental research design with nonrandomized pretest-post test group design method. Sample of 30 pregnant women with hypertension. The statistical test used the Paired Samples t-Test. The research results of Home blood pressure monitoring and Health Education were significantly effective in reducing the blood pressure of pregnant women, both systolic and diastolic values ​​with a p value of 0.000 (p < 0.05). Meanwhile, in the comparison group, the systolic p value was 0.000 (p<0.05), the diastolic value was 0.001 (p<0.05). The combination of HBPM and Health Education can help improve hypertension management and minimize complications due to recurrent hypertension in pregnant women.